1365 PROACTIVE IT-ASSISTED CGA IN CARE HOMES IMPROVES ADHERENCE TO PREFERRED PLACE OF CARE AND DEATH, HOSPITALISATION AND MORTALITY RATES. (16th January 2023) - Attwood, D; Vafidis, J; Boorer, J; Ellis, W; Earley, M; Denovan, J; Hart, G; Williams, M; Burdett, N; Lemon, M; Hope, S V
Abstract: Introduction: Primary care-based frailty identification and proactive comprehensive geriatric assessment (CGA) remains challenging. Our Devon-based Primary Care Network has developed and introduced an innovative, community-based IT-assisted CGA (i-CGA) process, which includes advance care planning (ACP). We wished to see if this process could improve effectiveness of ACP in residential care home (CH) residents. Methods/Intervention: 1) GPs clinically assessed all CH residents for frailty. 2) Proactive i-CGAs completed using our IT-assisted CGA tool, which prompts to review/consider/address: - previous CGA-related entries; - traditional CGA-domains/risks; - high-risk drugs/deprescribing; - ACP discussions (hospitalisation/resuscitation/place of death preferences) 3) ACPs shared with relevant healthcare services/Out-Of-Hours. Interim analysis focused on adherence to ACP-documentation in severely frail residents, comparing groups: i-CGA (1-year post-i-CGA completion) Control (1-year post-frailty diagnosis, no i-CGA, usual care) Results: i-CGA group: 196 residents (16 mild/69 moderate/111 severe frailty); control group: 100(13 mild/31 moderate/56 severe). No significant baseline differences. 100% residents in the i-CGA group had documented resuscitation decisions, vs 72% (72/100) controls: in 97% of both groups (191/196, 70/72) to 'allow a natural death'. 85% (94/111) severely frail i-CGA residents preferred not to be hospitalised. 55% (52/94) died, 90% (47/52) in their CH. Compared to the preceding year, unplanned hospitalisation rates fell:0.86 to 0.68/person years alive. In severely frail control residents, unplanned hospitalisations increased: 0.87 to 2.05/person years alive. 29% (16/56) had no hospitalisation preferences documented. 16/16 died, 25% (4/16) in hospital. 40/56 had documented decisions, not all recent:38% (15/40) wished for admission. Significant group mortality difference was seen: 55% (62/111) severely frail i-CGA residents died compared to 77% (43/56) controls, p=0.0013. Conclusions: Proactive primary care-led i-CGA in severely frail CH residents promotes up-to-date discussions regarding preferred place of care and death. Most prefer not to be hospitalised, despite traditionally high rates of unplanned admissions. Our i-CGA/ACP process improves adherence to preferences, reduces unplanned hospitalisations and mortality rates. Progressive i-CGA completion and annual/opportunistic reviews should confer progressive benefits.